Stilistic Study Of Poetry Anthology “Aku Ingin Menjadi Peluru” Wiji Thukul's Works - Yuannisah Aini Nasution; Mei Nanda Sari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This research focuses on study of diction, style of language, and imagery in the anthology of poetry "Aku ingin menjadi peluru" by Wiji Thukul. This research uses a qualitative approach in the form of qualitative narrative research using content analysis methods. The purpose of this research is to find out the depth of meaning in the document under study. This research uses qualitative research methods, namely the literary research method using stylistic research theory. The data source used in this study is the anthology of the poem "I want to be a bullet" by Wiji Thukul in 2004. The data collection technique in this study uses document analysis, which is to optimally utilize a set of procedures to draw valid conclusions and existing documents. Collecting data used in this research are by using library techniques, listening techniques, and note-taking techniques. The results of the analysis shows that stylistic forms found in “aku ingin jadi peluru” are (1) the choice of words (diction) using concrete words, (2) the use of synecdoche figure of speech, and (3) use of motion imagery